Sustaining Healthcare: Bridging Education with Biomedical and Healthcare Challenges - Papadopoulou, Paraskevi; Marouli, Christina; Misseyanni, Anastasia (European Journal of Sustainable Development, 2020)
Major advances and breakthroughs in Medicine and Healthcare are transforming our world. How will we manage to tackle our disease burden to improve our day-to-day well-being especially if in developed countries the global population of people over 80 will more than triple by 2050 and in the less developed ones the youth profile will escalate? Will Europeans as an example, find ways to balance budgets and restrain spending and come up with a sustainable survival strategy for Europe’s healthcare systems? This work addresses a number of challenging questions and offers “smart” solutions and a framework on how to develop and sustain new models of care and improve the public services profile with the vision to become globally leading healthcare institutions mainly in Europe and particularly in Greece. The nature of programs in biomedical and healthcare sciences, the kind of educators and healthcare professionals and how to technologically and practically support such programs is considered. How to connect Biomedical programs with Medical Centers and what kind of student internships can be developed is discussed. What it means to have patient-centered medical centers which abide by strict European and international guidelines and certifications and how to provide top quality medical services is also examined. Keywords: Education, Healthcare, Medicine, Biomedical Programs, Smart Solutions, Internships, International Certifications